Commonwealth-Government of Guyana programme for sustainable tropical forestry (Commonwealth Secretariat LondonGB, 1990)
Includes a report by a Commonwealth Group of Experts which contains the group's major recommendations on an action programme designed to promote the sustainable management of tropical rainforests. Gives also, a comprehensive description of the project site.
DC